Tracking the Trajectory of Functional Humoral Immune Responses Following Acute HIV Infection - Jennewein, Madeleine F.; Mabuka, Jennifer; Papia, Cassidy L.; Boudreau, Carolyn M.; Dong, Krista L.; Ackerman, Margaret E.; Ndung'u, Thumbi; Alter, Galit (Frontiers in Immunology, 2020)
Increasing evidence points to a role for antibody-mediated effector functions in preventing and controlling HIV infection. However, less is known about how these antibody effector functions evolve following infection. Moreover, how the humoral immune response is naturally tuned to recruit the antiviral activity of the innate immune system, and the extent to which these functions aid in the control of infection, are poorly understood. Using plasma samples from 10 hyper-acute HIV-infected South African women, identified in Fiebig stage I (the FRESH cohort), systems serology was performed to evaluate the functional and biophysical properties of gp120-, gp41-, and p24- specific antibody responses during the first year of infection. Significant changes were observed in both the functional and biophysical characteristics of the humoral immune response following acute HIV infection. Antibody Fc-functionality increased over the course of infection, with increases in antibody-mediated phagocytosis, NK activation and complement deposition occurring in an antigen-specific manner. Changes in both antibody subclass and antibody Fc-glycosylation drove the evolution of antibody effector activity, highlighting natural modifications in the humoral immune response that may enable the directed recruitment of the innate immune system to target and control HIV. Moreover, enhanced antibody functionality, particularly gp120-specific polyfunctionality, was tied to improvements in clinical course of infection, supporting a role for functional antibodies in viral control.